Mechanical Strength Analysis of Bamboo Fiber and Glass Powder Reinforced Composites Using Epoxy Matrix as an Alternative Visor - Al. Aziz. R, M. Shafwallah; Faizin, Kholis Nur; Gascoin, Nicolas; Fakhrudi, Yoga Ahdiat; Kurniawan, Pradhana (Journal of Mechanical Engineering, Science, and Innovation, 2025)
This study aims to analyze the mechanical strength of composites with bamboo fiber and glass powder reinforcement using an epoxy matrix. The study used a hand lay-up method with three variations of volume fraction composition, namely (1) 15% bamboo fiber, 15% glass powder, 70% resin, (2) 20% bamboo fiber, 10% glass powder, 70% resin, and (3) 25% bamboo fiber, 5% glass powder, 70% resin. The bamboo fiber used was the result of alkali treatment using 15% NaOH solution to remove lignin and cellulose, while the glass powder was obtained from household glass waste with a particle size of 60 mesh. Mechanical property testing included tensile testing (ASTM D638 Type 1), compression testing (ASTM D695-96), and impact testing (ASTM D256), while morphological structure analysis was carried out using Scanning Electron Microscope (SEM) testing. The results showed that the volume fraction composition of 25:5:70 produced the highest tensile strength with an average value of 95.69 N/mm² and the highest impact strength of 29.91 J/mm. Meanwhile, the composition of 15:15:70 obtained the highest compressive strength of 57.13 MPa. SEM analysis of the composite fracture showed the occurrence of full out fiber, debonding, and void phenomena in the matrix, which affected the decrease in the material strength value. This indicates that variations in the composition of bamboo fiber and glass powder can optimize the mechanical properties of composites, while supporting the utilization of natural materials and waste as environmentally friendly innovation materials for automotive applications, especially Yamaha Vixion motorcycle visor products.